INOVASI PEMBELAJARAN BERBASIS KONTEKS LOKAL SEBAGAI SOLUSI PENDIDIKAN DASAR DI DAERAH RURAL - Nadia Wahab, Ernina; Rahman, Abdul; Nurhaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary education in rural and disadvantaged areas (3T: underdeveloped, frontier, and outermost regions) still faces various challenges, including limited educational facilities, low access to technology, and learning processes that are less relevant to students’ daily lives. This study aims to examine local context-based learning innovation as a solution to improve the quality of elementary education in rural areas. The study employed a literature review approach by analyzing various scientific journals, books, and relevant educational policy documents. The findings indicate that local context-based learning is able to create more meaningful learning experiences by connecting learning materials with students’ environment, culture, and real-life experiences. Its implementation can be carried out through environment-based learning, local wisdom integration, Project-Based Learning (PJBL), Problem-Based Learning (PBL), as well as the development of local learning media and teaching materials. These approaches have been proven to enhance students’ learning motivation, creativity, critical thinking skills, and active participation. However, its implementation still faces challenges such as limited teacher competence, inadequate educational facilities, and insufficient policy support. Therefore, teacher training, the development of local-based teaching materials, and government support are needed to ensure that local context-based learning can be implemented optimally and sustainably in rural areas.